Ibn Rushd's Epistemology of Ijtihad in the Completion of Fiqh Ikhtilaf (Study of the Book of Bidayah Al-Mujtahid, Chapter of Worship) - Fauzi, Muhammad Rezky; Bakri, Muammar; Shuhufi, Muhammad (International Journal of Islamic Studies, 2023)
This study analyzes the nature and concept of Ibn Rushd's ijtihad in completing fiqh ikhtilaf among the ulama. He is known for his expertise in philosophy, logic, medical, and the fields of jurisprudence and jurisprudence (Islamic law). It can be proven in his monumental work "Bidayah al-Mujtahid wa Nihayah al-Muqtasid." This study conducted descriptive library research based on a normative theological approach. This study collected data from the primary source of the book "Bidayah al-Mujtahid wa Nihayah al-Muqtasid" and other relevant and related secondary sources and then analyzed it using content analysis techniques. The study results showed that: 1) Ibn Rushd has a rich experience and scientific background. He referred to many sources in his ijtihad that mostly came from the book al-Istiz\kar by Ibn Abd al-Bar, so those books influenced some of Ibn Rushd's ijtihad decisions. Thus, Ibn Rushd cannot be considered an absolute mujtahid. 2) Generally, he is still guided by the ijtihad methodology outlined critically by the Ulama. Meanwhile, there are some approaches to solve the problem of ikhtilaf, such as first, the al-jam'u approach (compromise); second, al-tarjih (selecting among the most substantial arguments); third, al-jam'u baina al-jam'i wa al -tarjih (a combination of the al-jam'u and al-tarjih approaches); fourth, tawaqquf (silence); fifth, al-takhyir (optional).